Role Iron in Diabetes mellitus type 2 of the patients in province Diwaniya - AL-Mohammad, Hussein Mahdi kreem (AL-Kindy College Medical Journal, 2019)
Background: Diabetes mellitus is a common health problem of the world. Iron may be a part of the cause of the disease and its ComplicationsObjectives: This study was designed to determine the relationship between the levels of iron indices  and diabetes mellitus type 2. Type 2Type of the study: Cross –sectional study.Methods: diabetes mellitus is clinical condition characterized by hyperglycemia due to the absolute or relative deficiency of insulin. It is also followed by pathological abnormalities like impaired insulin secretion, peripheral insulin resistance, and excessive hepatic glucose production. Although type 2 diabetes mellitus is a multiple etiological disease, emerging scientific evidences show there is somewhat related to the disease with iron metabolism Results: The study includes thirteen (15 female and 15 male)  patient  with  Diabetes mellitus and (15 male and 15 female ) as the control. In the present study, significantly increased (p < 0.05)   At ferretin , iron,  transferitin, transferin saturated  and significant decrease (p < 0.05) EIBS, TIBC  .Conclusions: These results suggest that the role negative of increase iron in development Diabetes mellitus by a number of  mechanisms.  .